Analisa Pertimbangan Hakim Terhadap Gugatan Perceraian yang Tidak Dapat Diterima: Niet Ontvankelijke Verklaard - Mennix Hamonangan; Zaenal Arifin (Jurnal Hukum dan Demokrasi (JHD), 2025)
In the course of a household, there are always disputes between husband and wife that cannot be resolved and lead to divorce. This study aims to determine the legal consequences of an unacceptable lawsuit in a case of contested divorce and to find out the judge's consideration in deciding an unacceptable lawsuit in a case of contested divorce. This research uses normative legal research methods with a case approach. The results showed that in Law Number 1 of 1974 concerning marriage in Article 39 paragraph (2) of the Marriage Law and its explanation stated that divorce can be carried out if it is in accordance with the reasons that have been determined. An unacceptable verdict (NO) is a verdict stating that the lawsuit cannot be accepted, due to formal defects. Then, the reasons that cause the lawsuit to be unacceptable due to formal defects are that the power of attorney is invalid, the lawsuit is filed by a party with no legal interest, the lawsuit is eror in persona, the lawsuit is beyond competence, the lawsuit is osbcuur libel, the lawsuit is premature and the lawsuit has expired. Obscuur Libel lawsuit is a vague or unclear lawsuit and the cause of the obscuur libel lawsuit in this case is that the petitum is not detailed, therefore the lawsuit cannot be accepted. the provision of unacceptable lawsuits in civil disputes is not regulated rigidly in a legislation but is a provision that develops in the practice of dispute resolution in court as a form of translation of previous judges as a form of derivation of procedural law principles. Decisions on the inadmissibility of lawsuits are in principle the same as other decisions, which have binding force, and are only void if canceled by a higher court, however, they have legal implications on several matters, namely: related to nebis in idem, the minimum limit of appeal which is only filed once, which means that there is a legal vacuum from these two issues, namely a new lawsuit with the same case that has been decided to be nebis or not.